2016
DOI: 10.11607/jomi.4325
|View full text |Cite
|
Sign up to set email alerts
|

Graftless Full-Arch Implant Rehabilitation with Interantral Implants and Immediate or Delayed Loading—Part I: Reconstruction of the Edentulous Maxilla

Abstract: To compare long-term survival and marginal bone loss of late interantral implants in the nonaugmented edentulous maxilla subjected to immediate vs delayed loading. Materials and Methods: One hundred twenty-two edentulous patients with implants in native, healed jawbone were subjected to either immediate loading (179 implants) or delayed loading (403 implants) of their four to six interantral implants (part I of 362 graftless maxillary cross-arch rehabilitations performed in the years 2004 to 2013). Kaplan-Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Twelve studies compared immediate and conventional loading protocols. From these, four studies were RCTs, five were prospective studies, and three were retrospective studies . Four studies compared early loading and with conventional loading, from which two were RCTs and two were retrospective studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies compared immediate and conventional loading protocols. From these, four studies were RCTs, five were prospective studies, and three were retrospective studies . Four studies compared early loading and with conventional loading, from which two were RCTs and two were retrospective studies .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 observational studies included in this systematic review, three received a 12‐point score, two studies received an 11‐point score out of a total of 14 points (high methodological quality); two studies received a 10‐point score, one article received a 9‐point score, and one article received an 8‐point level according to the methodological quality. Regarding “selection of study groups,” none of the studies reported any form of sample size calculation.…”
Section: Resultsmentioning
confidence: 99%
“…In studies that compared the immediately loaded implants with conventionally loaded implants, the results showed high survival rates in both groups. The first part of a study about late inter-antral implantation in the nonaugmented edentulous maxilla reported survival rates of 98.3% in the immediate loaded implants group and 96.7% in the conventional group at a mean observation period of 4.7 years [ 32 ]. The results in the second part of the study, in cases of immediate inter-antral implantation, also showed similar findings.…”
Section: Reviewmentioning
confidence: 99%
“…When immediate loading four implants with a pre-existing denture converted to a fixed dental prosthesis compared with conventional loading (3–6 months), it was reported that the same change of 1.2 mm in marginal bone over 5 years in both groups was observed [ 39 ]. Also an insignificant difference in mean MBL between the two treatment modalities in both late and immediate inter-antral implantation in the nonaugmented edentulous maxilla was reported [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…In most of the approaches used for the rehabilitation of an edentulous maxilla with implants, 4 to 6 implants have to be placed in the interantral area [[9], [10], [11]]. The interantral alveolar bone borders distally on variously pneumatized maxillary sinuses and contains the canine and incisor area in 96.9% of individuals [8].…”
Section: Introductionmentioning
confidence: 99%